Exploratory descriptive analysis of opioid prescribing prevalence of nurse practitioners and the specialties associated with the top prescribers. Issue 6 (5th May 2020) - Pan, Kevin; Collins, Andrea
Abstract: Background: Opioid prescription drug abuse is increasingly becoming a concern beyond the United States. Little is known regarding nurse practitioners' opioid prescribing patterns or settings. Aim: To examine nurse practitioners' opioid prescription patterns. Methods: We conducted a retrospective cross‐sectional descriptive study of the 2016 Medicare Part D Prescriber Public Use File and analysed the association between the number of nurse practitioners and the number of opioid prescriptions. We conducted Web searches on the top 1% of prescribers to obtain the specialty areas in which nurse practitioners worked. Results: There was no significant correlation between the prevalence of nurse practitioners and the opioid prescription rates among the states in the United States. Most nurse practitioners do not prescribe opioids. Opioid prescription is highly concentrated among nurse practitioners, as 1% of nurse practitioners account for one third of opioids prescribed by nurse practitioners. Most of the top 1% opioid prescribers practice in specialty care with board‐certified pain medicine physicians. Conclusions: The prevalence of nurse practitioners is not likely a significant contributing factor to the opioid epidemic. Rather than increased scrutiny of opioid prescribing, a better approach to curb the opioid crisis might be to facilitate collaboration among physicians, nurse practitioners and patients. SUMMARY STATEMENT: What is already known about this topic? Opioid prescription drug abuse is increasingly becoming a concern beyond the United States. Little is known regarding nurse practitioners' (NPs') opioid prescribing patterns or settings. What this paper adds? There is no significant correlation between prevalence of NPs and total amount of opioid prescriptions. Most NPs do not prescribe opioids; opioid prescription is highly concentrated in a small portion of NPs. Many of the top 1% opioid prescribing NPs do not work in primary care but in specialty care with pain management physicians. The implications of this paper: Promoting the NP profession could help curb the opioid crisis as most NPs do not prescribe opioids. To combat the opioid crisis, policies should encourage collaborative patient care where physicians work with NPs synergistically. There may be countries where these results could help design NP prescribing policies.